Ecosystem services and biomass stock from bamboo stands in central and southern Benin, West Africa - HOUDANON, Roel Dire; Mensah, Sylvanus; GNANGLE, Césaire; YOROU, Nourou Soulemane; Houinato, Marcel (My University, 2018)
Bamboo is a multi-purpose woody grass with international and national interests accentuated by the promotion of green energy. In Asia, bamboo plantations are being successfully promoted and constitute important carbon sinks, while in Africa, they remain unimproved despite their potential service supply. In this study, we assessed ecosystem services (ESs) and biomass stock from bamboo stands in central and southern Benin. First, we interviewed 264 informants across seven sociolinguistic groups from 10 municipalities to analyse ESs importance across gender and multi-linguistic group spaces and determine trade-offs and synergies between services. Sec- ond, we used ﬁeld plots to quantify biomass stocks in selected bamboo stands. Seven ESs (building material, handicraft material, medicine, ﬁrewood, support for agri- culture, biological control and cultural dance) were men- tioned, with provisioning ESs being the most important. ESs were equally mentioned by women and men, except for ﬁrewood and medicine which showed slightly different patterns. Handicraft material, ﬁrewood and cultural dance were mostly mentioned by Nago and Fon, whereas bio- logical control and support for agriculture were cited by Tofﬁn and Weme. Handicraft material, ﬁrewood and cul- tural dance were synergistically mentioned, but negatively associated with citations of biological control and support for agriculture, suggesting trade-offs. The estimated bio- mass density was remarkably low, ranging from 0.54 to 29.7 t/ha, with an average value of 11.1 t/ha. These results show a need for participative management integrating sociolinguistic groups into decision-making processes while promoting extensive bamboo plantations and bam- boo carbon farming.
Keywords: Biomass Cultural valuation Gender Local; perception Sociocultural group